(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The Companions And Their Justice And Defending Them At Al_Imam Al Kortobi Al-Maliki, His Statements Came On Many Ways. Al_Imam Al Kortobi Al-Maliki Showed The Status Of The Companions Through The Islamic Texts That Indicate This Status With His Talks About It. Also He Showed The Obligation On Their Justice, As Provided By The Islamic Texts And Blessing Them.This Led To Defend On The Companions By Al-Imam Al Kortobi Al-Maliki. Through This Research There Are A Great Efforts Of Al Imam Al Kortobi In Defending On The Companions And Showing Their Status. He Had A Wonderful Position Towards The Companions Of The Messenger Of Allah. He Was With Ahl Al Sunna In This Subject, That Was A Good Thing For Him Till The Ddoomsday. The Most Important Results Of This Research In The Following Matters: - Al Imam Al Kortobi Gave A Great Cere To The Companions In His Writings, Praise Them And Raise Their Status. - Also He Has A Clear Efforts In Showing The High Status Of The Companions. - His State Of The Justice Of The Companions Throughout The Islamic Texts That Indicate This. - His Great Love Of The Companions Appears Through His Defense Praise Them. Key Words- Al Kortobi,Showing,Status,The Companions,Defense